Toxoplasma gondii immunoglobulin G in paired infant-and-mother sera - Ayling Sanjaya; Nurhayati Masloman; Rocky Wilar; Josef Tuda (Indonesian Pediatric Society, 2009)
Background Toxoplasmosis is a worldwide zoonotic diseasecaused by Toxoplasma gondii. Congenital toxoplasmosis (CT)is the result of vertical transmission during pregnancy thatmay cause pathologic effects on the newborn such as classicaltriad of congenital toxoplasmosis. Newborn humans are notimmunologically competent and the infant must be protected by passive lgG antibodies that are selectively transported across the placenta during development. We studied the transfer of passive lgG from the mother to developing infant using blood specimen taken from the infant within one month of birth.Objective To determine the seropositivity of lgG to T. gondii in paired sera of infants and mothers.Methods A cross sectional study was carried out on 50 pairedsera of infants of less than one month of age and their mothers. The study was carried out between November 2007 and January 2008 at Prof. R. D. Kandou Hospital in Manado. T. gondii lgG was detected using the Latex Agglutination method. The seropositivity ofT. gondii lgG was analyzed descriptively.Results A total of 28 mothers from 50 infant-mother pairs wereseropositive for T. gondii IgG. Of the 28 seropositive mothers, 22 of their paired infants were seropositive. The remaining six seropositive mothers had infants that were not seropositive for T. gondii.Conclusions The identification of seropositive lgG for T. gondii in infants less than one months age indicates that the lgGs in infants are mostly derived from their mothers. CT must be considered and further examinations are needed.